Preparation method of high-pressure-resistant high-flux alumina ceramic nanofiltration membrane support
Through high-pressure hydrothermal method and microwave low-temperature sintering technology, combined with corn starch and PVA, the problem of easy rupture of ceramic nanofiltration membrane in high-pressure and chemical corrosion environments is solved, and the pressure resistance strength and pure water flux of ceramic membrane support are improved. , realizes the stability and efficient application of ceramic films.
Patent Information
- Application Number
- CN202411246193.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
AI Technical Summary
Existing ceramic nanofiltration membranes are prone to rupture under high pressure and chemical corrosion environments, and the aggregation of sintering aids leads to low strength and unstable performance of ceramic membrane tubes, and lacks effective solutions to improve their service life and stability.
The nanotitanium oxide is uniformly wrapped in the surface and internal cracks of alumina ceramic particles by high-pressure hydrothermal method, and through microwave low-temperature sintering technology, combined with the use of corn starch and PVA, it forms a high-pressure and high-throughput alumina ceramic nanofiltration membrane support. body.
It significantly improves the pressure resistance strength and pure water flux of the ceramic membrane support, reduces defects and inhomogeneity, extends service life, solves the problem of membrane tubes prone to fracture under high operating pressure, and is a large nanopore ceramic membrane. Large-scale application provides technical support.
Smart Images

Figure CN119215687A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic membrane support preparation, and in particular relates to a method for preparing a high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support. Background Art
[0002] Membrane technology and its related processes are a high-tech field that has rapidly emerged in the middle of the last century. They are currently highly valued worldwide and are regarded as key areas for scientific and technological innovation and national economic development. Compared with traditional polymer separation membranes, ceramic nanofiltration membranes have been widely used in industries such as petrochemicals, food processing, wastewater treatment, pharmaceutical technology, and energy due to their high filtration accuracy, and have gradually become one of the key technologies in my country's industrial transformation and upgrading.
[0003] However, the application of ceramic nanofiltration membranes in harsh environments faces many challenges. These environments usually have the following characteristics: First, high-pressure operation is necessary. In high-precision industrial filtration and separation processes, it is usually necessary to operate under high-pressure conditions to improve filtration efficiency and processing capacity. However, ceramic nanofiltration membranes currently on the market are prone to rupture under high operating pressures, which affects their service life. Secondly, chemical corrosion is a problem. When dealing with liquids containing strong acids, strong alkalis or organic solvents, ceramic nanofiltration membranes must have good chemical resistance. However, existing ceramic membrane supports may form internal cracks during the preparation process. These cracks are easily expanded and chemically corroded during use, resulting in membrane tube rupture. Finally, mechanical vibration and impact are also common problems in practical applications. The ceramic nanofiltration membrane support is often affected by these external forces, which may cause the expansion of internal cracks, thereby causing the membrane support to rupture.
[0004] In the current ceramic nanofiltration membrane support preparation process, it is necessary to add nano sintering aids to reduce the sintering temperature of the support. Usually, the sintering aid is added by direct mechanical mixing. However, the nano sintering aid particles are easy to agglomerate, which may lead to uneven mixing of the sintering aid and the large-particle ceramic powder of the support, and segregation is easy to occur during the sintering process, resulting in low strength and large fluctuations of the ceramic membrane tube, and unstable performance (such as Figure 1As shown). In addition, since the defect cracks of the ceramic aggregate particles are narrow and the surface is easy to absorb air and moisture after the cracks are broken, the agglomerated sintering aid cannot penetrate into the cracks or adhere to the crack surface. During the sintering process of the support body, the cracks inside these aggregate particles are not covered by the sintering aid, and the sintering temperature cannot reach the melting temperature, resulting in the inability to repair the cracks or sinter together, forming internal crack defects in the finished ceramic nanofiltration membrane support body. These crack defects are very susceptible to external force vibration during the transportation and high-pressure use of the membrane tube, causing crack expansion, resulting in the breakage and scrapping of the ceramic membrane tube. At the same time, the crack defects inside these particles are also susceptible to chemical corrosion during use, which seriously affects the safety and service life of the ceramic membrane tube. These problems ultimately lead to a series of problems such as many defects in the prepared support body, low pass rate, poor product stability, and easy breakage of the membrane tube under the high operating pressure of the ultrafiltration process, which seriously restricts the large-scale application and promotion of nanopore ceramic membranes. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support comprises the following steps:
[0008] (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-titanium oxide dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-titanium oxide in the nano-titanium oxide dispersion is 5-20 nm;
[0009] (2) drying the material obtained in step (1), and then sintering it once at 650-850° C. for 25-35 min using a microwave heating device to obtain alumina powder;
[0010] (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged;
[0011] (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding;
[0012] (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1750-1880° C. for 3-5 h to obtain the high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
[0013] In a preferred embodiment of the present invention, in step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%.
[0014] In a preferred embodiment of the present invention, the drying temperature in step (2) is 120° C. and the drying time is 4 hours.
[0015] In a preferred embodiment of the present invention, the screening in step (3) is through a 120-500 mesh sieve.
[0016] In a preferred embodiment of the present invention, in step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.
[0017] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.
[0018] In a preferred embodiment of the present invention, in step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.
[0019] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.
[0020] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.
[0021] A ceramic nanofiltration membrane comprises a high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support body obtained by the above-mentioned preparation method.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention firstly adopts a high-pressure hydrothermal method to uniformly wrap the nanoparticles on the surface of alumina ceramic particles and fill them into the crack defects inside the particles; then, the microwave low-temperature rapid one-time sintering technology is used to stably and rapidly combine the nano-titanium oxide particles with the surface and internal cracks of large-particle alumina ceramic powders through a uniform and rapid heating process combined with the high wave absorption efficiency of nano-titanium oxide particles (this efficiency exceeds that of large-particle α-alumina). This treatment effectively avoids the problems of nano-particle desorption, agglomeration and segregation that may occur during subsequent mixing, molding and sintering, thereby reducing the defects and non-uniformity of the ceramic membrane support. In addition, compared with traditional heating methods, microwave heating achieves a more uniform temperature distribution and prevents abnormal agglomeration and growth of nano-crystals.
[0024] 2. The present invention uses only nano-titanium oxide as a sintering aid and utilizes the high hydrophilicity of titanium oxide to significantly improve the pure water flux of the alumina ceramic membrane support.
[0025] 3. The high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support prepared by the present invention has significantly improved compressive strength and pure water flux. It not only solves the problems of many microscopic defects, low qualified rate, and poor product stability of existing conventional ceramic nanofiltration membrane supports, but also effectively responds to the challenge of easy breakage of membrane tubes under high operating pressure in ultrafiltration processes, providing a solid technical guarantee for the large-scale application and promotion of nanopore ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope photograph of a ceramic nanofiltration membrane support body prepared by the existing ceramic nanofiltration membrane support body preparation process in the background technology of the present invention.
[0027] Figure 2 This is a scanning electron microscope photograph of the alumina powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0029] Example 1
[0030] (1) mixing large-particle alumina ceramic powder (Al2O3 purity> 99.8%, average particle size 10 μm) with nano-titanium oxide dispersion (concentration 8 wt%, TiO2 purity> 99.9%, average particle size 5 nm), and reacting under high pressure (16 MPa) hydrothermal (350°C) conditions for 4 h;
[0031] (2) The material obtained in step (1) was dried at 120° C. for 24 h, and then sintered at 650° C. for 30 min using a microwave heating device to obtain alumina powder (such as Figure 2 As shown, microwave heating avoids the problems of uneven temperature distribution and abnormal agglomeration and growth of nano-grains);
[0032] (3) After passing the alumina powder obtained in step (2) through a 500-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76wt%:3wt%:2wt%:16wt%:3wt%.
[0033] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.
[0034] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1750° C. for 3 hours to obtain the high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
[0035] (6) coating one or more layers of filtration membrane on the high-pressure resistant and high-throughput alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.
[0036] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 31MPa, and pure water flux of 8500LMH. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made of the same raw materials by simple mechanical mixing has a burst pressure resistance of only 12MPa, and a pure water flux of 3500LMH.
[0037] Example 2
[0038] (1) mixing large-particle alumina ceramic powder (Al2O3 purity> 99.8%, average particle size 45 μm) with nano-titanium oxide dispersion (concentration of 6 wt%, wherein the purity of TiO2 is> 99.9%, and the average particle size is 20 nm), and reacting them under high pressure (8 MPa) hydrothermal (300°C) conditions for 4 h;
[0039] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 850° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);
[0040] (3) After passing the alumina powder obtained in step (2) through a 120-mesh sieve, the alumina powder, corn starch (average particle size of 1 μm) and PVA (average particle size of 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 80wt%: 3wt%: 2wt%: 13wt%: 2wt%.
[0041] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.
[0042] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1880° C. for 5 hours to obtain the high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
[0043] (6) coating one or more layers of filtration membrane on the high-pressure resistant and high-throughput alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.
[0044] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 28MPa, and pure water flux of 10500LMH. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made of the same raw materials by simple mechanical mixing has a burst pressure resistance of only 8MPa, and a pure water flux of 5500LMH.
[0045] Example 3
[0046] (1) mixing large-particle alumina ceramic powder (Al2O3 purity> 99.8%, average particle size 30 μm) with nano-titanium oxide dispersion (concentration of 5 wt%, wherein the purity of TiO2 is> 99.9%, and the average particle size is 15 nm), and reacting them under high pressure (13 MPa) hydrothermal (330°C) conditions for 4 h;
[0047] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 750° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);
[0048] (3) After passing the alumina powder obtained in step (2) through a 200-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 78wt%: 3wt%: 2wt%: 15wt%: 2wt%.
[0049] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.
[0050] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1830° C. for 4 hours to obtain the high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
[0051] (6) coating one or more layers of filtration membrane on the high-pressure resistant and high-throughput alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.
[0052] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 29MPa, and pure water flux of 10000LMH. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made of the same raw materials by simple mechanical mixing has a burst pressure resistance of only 10MPa, and a pure water flux of 4500LMH.
[0053] According to the above embodiments, the support prepared by the present invention can withstand a bursting pressure of 28-32 MPa. The pure water flux of the support can reach 8000-11000 LMH. In contrast, the alumina ceramic nanofiltration membrane support prepared by the prior art method has a bursting pressure of only 8-15 MPa and a pure water flux of only 3000-6000 LMH.
[0054] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support, characterized in that: The steps include: (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-titanium oxide dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-titanium oxide in the nano-titanium oxide dispersion is 5-20 nm; (2) drying the material obtained in step (1), and then sintering it once at 650-850° C. for 25-35 min using a microwave heating device to obtain alumina powder; (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged; (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding; (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1750-1880° C. for 3-5 h to obtain the high-pressure resistant and high-flux alumina ceramic nanofiltration membrane support.
2. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%.
3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 4 hours.
4. The preparation method according to claim 1, characterized in that: The sieving in step (3) is through a 120-500 mesh sieve.
5. The preparation method according to claim 1, characterized in that: In the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.
6. The preparation method according to claim 5, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.
7. The preparation method according to claim 1, characterized in that: In the step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.
8. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.
9. The preparation method according to claim 8, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.
10. A ceramic nanofiltration membrane, characterized in that: The invention comprises a high-pressure-resistant and high-flux alumina ceramic nanofiltration membrane support body prepared by the preparation method described in any one of claims 1 to 9.
